Some Biochemical and Histopathological Changes in Liver of Pregnant Female Rats Following Fluoroquinolones Administration - Ashwaq Jabbar Al-Miahy (University of Thi-Qar Journal of Science, 2019)
The present study was designed to investigate the possible effects of fluoroquinolones (Norfloxacin,Ciprofloxacin, and Enrofloxacin) on some biochemical and histopathological changes of liver in pregnant female rats(Ratus norvigicus). 40 pregnant rats weighing 175-185 gm, and 10-12 weeks old in age, were divided equally in tocontrol and three experimental groups. Control group treated with dimethylsulphoxide (DMSO) at a dose 0.5ml/animal/day while the experimental animals treated with oral doses of (700 mg/Kg b.w. of Norfloxacin, 550mg/Kg b.w. of Ciprofloxacin, and 750 mg/Kg b.w. of Enrofloxacin, all groups were administered these substancesfrom the day 1 till the day 15 of gestation. Dissection was performed on day 15 of gestation after 4 hours from thelast dose. Results revealed a significant (p<0.05) decrease in total protein content in serum of the treated groups(NFX, CPX) when compared with control, while ENX treated group showed a decrease in total protein but notsignificant. Assessment of globulin in all treated groups showed a significant decrease as compared with the globulinof control. Histopathological changes in liver sections of these females were in the form of dilatation of central andportal vein, and sinusoidal spaces, congestion in blood vessels, degenerated hepatocytes with necrotic nuclei. Theseresults revealed the toxic effects of fluoroquinolones on the livers of pregnant female rats.